Proteoglycans in Obesity-Associated Metabolic Dysfunction and Meta-Inflammation - Pessentheiner, Ariane R.; Ducasa, G. Michelle; Gordts, Philip L. S. M. (Frontiers in Immunology, 2020)
Proteoglycans are a specific subset of glycoproteins found at the cell surface and in the extracellular matrix, where they interact with a plethora of proteins involved in metabolic homeostasis and meta-inflammation. Over the last decade, new insights have emerged on the mechanism and biological significance of these interactions in the context of diet-induced disorders such as obesity and type-2 diabetes. Complications of energy metabolism drive most diet-induced metabolic disorders, which results in low-grade chronic inflammation, thereby affecting proper function of many vital organs involved in energy homeostasis, such as the brain, liver, kidney, heart and adipose tissue. Here, we discuss how heparan, chondroitin and keratan sulfate proteoglycans modulate obesity-induced metabolic dysfunction and low-grade inflammation that impacts the initiation and progression of obesity-associated morbidities.